1990
DOI: 10.1002/jcp.1041450209
|View full text |Cite
|
Sign up to set email alerts
|

The Na+,K+,2Cl‐cotransport system in HeLa cells: Aspects of its physiological regulation

Abstract: We have previously reported on the biochemical properties of a Na+,K+,2Cl-cotransport system in HeLa cells and here we deal with aspects of its physiological regulation. Na+,K+,2Cl-cotransport in HeLa cells was studied by 86Rb+ influx and 86Rb+/22Na+ efflux measurements. The effects of rat atrial natriuretic peptide (ANP), isoproterenol, and amino acids on 86Rb+ flux, mediated by the bumetanide-sensitive Na+,K+,2Cl-cotransport system and the ouabain-sensitive Na+/K(+)-pump, were investigated. ANP reduced bumet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…3C). Bumetanide only slowed down vacuolation: after a sufficient time NRU reached a nearly maximal value, in agreement with the existence of other Cl − entry pathways into the cell [15].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…3C). Bumetanide only slowed down vacuolation: after a sufficient time NRU reached a nearly maximal value, in agreement with the existence of other Cl − entry pathways into the cell [15].…”
Section: Resultssupporting
confidence: 77%
“…3.3. Inhibition of the Na + , K + , 2Cl 3 cotransporter (NKCC) decreases vacuole development NKCC is the major entry pathway of Cl 3 into HeLa cells [15]. The antagonists of NKCC such as bumetanide [16] inhibited HeLa vacuolation due to VacA (Fig.…”
Section: Extracellular CL 3 Is Required For Cell Vacuolation Inducedmentioning
confidence: 99%
“…20 and 45). Activation of NKCC1 by hypertonicity has been historically demonstrated through bumetanide-sensitive unidirectional K ϩ influx measurements (e.g., 5,19,27,30,37,39,51,56). In a recent study performed in Xenopus laevis oocytes injected with mouse NKCC1 cRNA (17), we showed that hypertonicity stimulated bumetanide-sensitive K ϩ and Cl Ϫ influxes, but with a unidirectional K ϩ :Cl Ϫ transport ratio of 1:1.…”
mentioning
confidence: 76%
“…For this calculation, we considered only Na + , K + , Cl À , and NH 4 + . Intracellular concentrations of Na + , K + , and Cl À were assumed to be 44, 149 and 45 mM, respectively [26]. The mean ionic activity coefficients c for the external solution and cell cytoplasm were estimated using the solution ionic strength, I=( P c i z i 2 )/2, in an equation based on the Debye-Hu¨ckel theory (Eq.…”
Section: Discussionmentioning
confidence: 99%